Deposition of Ni/TiN composite coatings by a plasma assisted MOCVD using an organometallic precursor - Maiyalagan, Thandavarayan (2013)
Titanium nitride (TiN)/nickel (Ni) composite coatings were synthesized by plasma assisted metal-organic chemical vapour deposition (PAMOCVD) using organo-metallic and metal-organic complexes namely dichlorobis( 5- cyclopentadienyl)titanium (IV) for titanium and N,N'-ethylene-bis(2,4-pentanedion-iminoato)nickel(II) for nickel. The growth of such films was investigated in nitrogen (N2) plasma environment in the substrate temperature range of 450- 550ºC at a deposition pressure of 0.5-1 mbar. Prior to the deposition of films, the Ti precursor was subjected to the equilibrium vapour pressure measurements by employing TG/DTA in transpiration mode, which led to the value of 109.2 ± 5.6 kJ mol-1 for the standard enthalpy of sublimation (ΔHo sub). The phase identification using glancing incidence x-ray diffraction showed Ni/TiN is a nanocomposite coating containing nanocrystals of Ni and TiN with face centered cubic structure. Scanning electron microscopy revealed a uniform surface morphology of the films, while chemical analysis by energy dispersive analysis confirmed the presence of titanium, nickel and nitrogen in the composite films.